2014
DOI: 10.1002/anie.201309584
|View full text |Cite
|
Sign up to set email alerts
|

Nickel‐Catalyzed CH Alkylations: Direct Secondary Alkylations and Trifluoroethylations of Arenes

Abstract: A versatile nickel catalyst allowed for C-H alkylations of unactivated arenes with challenging secondary alkyl bromides and chlorides. The high catalytic efficacy also set the stage for direct secondary alkylations of indoles as well as C-H trifluoroethylations with ample substrate scope.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
111
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(115 citation statements)
references
References 75 publications
1
111
0
3
Order By: Relevance
“…21b Ackermann recently reported on the nickel(II)-catalyzed alkylation with secondary alkyl halides and trifluoroethylation of CH bonds using an 8-aminoquinoline as the directing group (Scheme 5). 23 The more active nickel source for this type of transformation was [(DME)NiCl 2 ] (DME: dimethoxyethane) with BDMAE [bis(2-dimethylaminoethyl) ether] as the stabilizing ligand using LiO t Bu as a base in toluene at 160°C for 20 h. The catalytic system tolerated a variety of functional groups with excellent selectivities for monoalkylated products. The metasubstituted amides gave 81 and 84 exclusively through the cleavage of the less-hindered CH bonds.…”
mentioning
confidence: 99%
“…21b Ackermann recently reported on the nickel(II)-catalyzed alkylation with secondary alkyl halides and trifluoroethylation of CH bonds using an 8-aminoquinoline as the directing group (Scheme 5). 23 The more active nickel source for this type of transformation was [(DME)NiCl 2 ] (DME: dimethoxyethane) with BDMAE [bis(2-dimethylaminoethyl) ether] as the stabilizing ligand using LiO t Bu as a base in toluene at 160°C for 20 h. The catalytic system tolerated a variety of functional groups with excellent selectivities for monoalkylated products. The metasubstituted amides gave 81 and 84 exclusively through the cleavage of the less-hindered CH bonds.…”
mentioning
confidence: 99%
“…Notably, many biologically active molecules, including the widely prescribed afloqualone, fluticasone propionate, and the anaesthetic sevoflurane, contain a CH 2 F group as an essential motif. [3] Although a variety of methods for the transition-metalcatalyzed trifluoromethylation [4] and difluoromethylation [3b, 5] of arenes have been developed in the past several decades, the incorporation of methyl groups containing a single fluorine (CH 2 F) into arenes has been studied to a lesser extent and remains a challenge. [6] The only example of a palladiummediated direct monofluoromethylation of pinacol phenylboronate was reported by the Suzuki group in 2009.…”
mentioning
confidence: 99%
“…(2), Scheme 4), which further implicated the generation of the fluoro(phenylsulfonyl)methyl radical in the catalytic cycle. Furthermore, catalytic (5 mol %) and stoichiometric amounts of [Ni(PPh 3 ) 4 ] were subjected to the standard conditions, respectively, but gave none or only trace amounts of 3 a, thus indicating that the Ni 0 species might not be involved in the catalytic cycle (see the Supporting Information for a detailed discussion).…”
mentioning
confidence: 99%
“…However, Ackermann recently successfully found the optimal reaction conditions for the Ni(II)-catalyzed alkylation of C-H bonds with secondary alkyl halides using essentially the same chelation system (Scheme 8) [32]. The reaction gave the monoalkylation products 22 with excellent selectivity.…”
Section: )-H Bondsmentioning
confidence: 99%
“…It was found that a variety of groups, such as alkyl, benzyl, allyl, and methyl groups, can be installed at the ortho-position in the Ni-catalyzed reaction of C-H bonds with alkyl halides or pseudohalides (Schemes 6 and 8) [29,30,32]. Zeng recently reported on the Ni(0)-catalyzed ortho-allylation of C-H bonds in aromatic amides using an 8-aminoquinoline as the directing group with allyl phosphates (Scheme 9) [33].…”
Section: )-H Bondsmentioning
confidence: 99%